Study on mechanism of carbonaceous gold ore during oxidation roasting by kinetics: phase transformation and structure evolution - Hui Li; Jianping Jin; Yuexin Han; Wei Xiao; Zhenya Zhou (Materials Research Express, 2021)
The pretreatment and effective utilization of carbonaceous gold ore is of significant to refractory gold resources. In this work, the calcination kinetics was employed to investigate the relationship between phase transformation and structure evolution of carbonaceous gold ore during roasting process. Mechanism functions were determined and the fact that roasting process was controlled by chemical reaction in the initial 90 min and dominated by internal diffusion as time reached to 120 min was uncovered. In addition, the apparent activation energies for initial and latter roasting stage were 212.11 kJ·mol ^−1 and 163.73 kJ·mol ^−1 , respectively. Combined with the analysis of phase transformation and structure evolution, the removal of carbonaceous matter and appearance of new tiny pores contributed to the change of calcination kinetics. Moreover, phase transformation and structure evolution were beneficial for elevating Au recovery during leaching experiment. These findings helped to understand the mechanism of carbonaceous minerals during roasting and provided new insight for the utilization of refractory gold resource.